Targeting EZH2 methyltransferase activity in ARID1A mutated cancer cells is synthetic lethal - Biter, Benjamin G. (Nat Med, 2015)
ARID1A, a chromatin remodeler, shows one of the highest mutation rates across many cancer types. Notably, ARID1A is mutated in over 50% of ovarian clear cell carcinomas, which currently has no effective therapy. To date, clinically applicable targeted cancer therapy based on ARID1A mutational status has not been described. Here we show that inhibition of the EZH2 methyltransferase acts in a synthetic lethal manner in ARID1A mutated ovarian cancer cells. ARID1A mutational status correlates with response to the EZH2 inhibitor. We identified PIK3IP1 as a direct ARID1A/EZH2 target, which is upregulated by EZH2 inhibition and contributes to the observed synthetic lethality by inhibiting PI3K/AKT signaling. Significantly, EZH2 inhibition causes regression of ARID1A mutated ovarian tumors in vivo. Together, these data demonstrate for the first time a synthetic lethality between ARID1A mutation and EZH2 inhibition. They indicate that pharmacological inhibition of EZH2 represents a novel treatment strategy for ARID1A mutated cancers.